Simulation Training Regarding Vaginal Delivery Versus Traditional Medical Student Clinical Education. (October 2017) - Stetzer, Brad; Sarfoh, Vanessa; Mercer, Brian; McKenzie, Margaret; Hueppchen, Nancy
Abstract : OBJECTIVE: To assess the impact of birth simulation training on medical student comfort, confidence and anxiety in performing a delivery, and knowledge of normal labor. METHODS: In this prospective study of 3rd-year medical students during their 4-week inpatient clinical experience, student groups were randomly assigned to "traditional" teaching versus traditional plus additional "simulation" teaching. All students were immersed in clinical experiences in the delivery room after an initial group education session regarding normal labor and delivery mechanisms and procedures. The group assigned to "simulation" underwent additional supervised simulation training for normal delivery and delivery complications. All groups underwent a pretest before training and a posttest on completion of their clinical rotation. Evaluated variables included: confidence and anxiety regarding performing a delivery; comfort controlling the head, shoulders and body during delivery; comfort in delivering a placenta; and knowledge of cardinal movements and stages of labor. Statistical analyses were accomplished using Pearson χ 2 analysis and Student's T tests. RESULTS: Sixty students participated. Overall, both traditional teaching and simulation groups demonstrated significant improvements in their scores regarding measures of comfort, anxiety, and knowledge between the pre- and posttests ( P ⩽0.05). However, comparison of posttest responses did not reveal those undergoing additional simulation training to have higher comfort or confidence in performing a vaginal delivery ( P >.05), or have lower anxiety at being involved in a vaginal delivery ( P >.05). Similarly, knowledge about the cardinal movements of labor and stages of labor at the posttest were similar between groups ( P >.05). CONCLUSION: In the context of an inpatient clinical rotation in which student comfort, confidence, anxiety, and knowledge regarding vaginal delivery improved significantly with traditional teaching, additional simulation training was not associated with improved outcomes.